2021
DOI: 10.1016/j.dcn.2021.101018
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ventromedial Prefrontal Cortex Activity in Adolescence Benefits Prosocial Reinforcement Learning

Abstract: Learning which of our behaviors benefit others contributes to forming social relationships. An important period for the development of (pro)social behavior is adolescence, which is characterized by transitions in social connections. It is, however, unknown how learning to benefit others develops across adolescence and what the underlying cognitive and neural mechanisms are. In this functional neuroimaging study, we assessed learning for self and others (i.e., prosocial learning) and the concurring neural track… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…Prior studies using probabilistic learning tasks have shown repeatedly that the striatum is involved in tracking social reinforcement learning signals for self and others while individuals receive outcomes (Lockwood, 2016;Westhoff et al, 2021), particularly when receiving rewards (Dugré et al, 2018;Oldham et al, 2018), while losses are associated more closely with the dorsal striatum (Dugré et al, 2018;Murray et al, 2022). Another area that has been implicated in reinforcement learning while receiving outcomes for self and others is the PFC (Khamassi et al, 2013;Javadi et al, 2014;Lockwood and Wittmann, 2018;Westhoff et al, 2021), both while receiving rewards (Lockwood et al, 2018) and losses (Dugré et al, 2018). Previous studies further suggest that rostral and subgenual regions of the mPFC might be specialized in learning for others in social contexts (Lockwood et al, 2016;Christopoulos & King-Casas, 2015).…”
Section: Learning How Behavior May Benefit Self and Othersmentioning
confidence: 99%
“…Prior studies using probabilistic learning tasks have shown repeatedly that the striatum is involved in tracking social reinforcement learning signals for self and others while individuals receive outcomes (Lockwood, 2016;Westhoff et al, 2021), particularly when receiving rewards (Dugré et al, 2018;Oldham et al, 2018), while losses are associated more closely with the dorsal striatum (Dugré et al, 2018;Murray et al, 2022). Another area that has been implicated in reinforcement learning while receiving outcomes for self and others is the PFC (Khamassi et al, 2013;Javadi et al, 2014;Lockwood and Wittmann, 2018;Westhoff et al, 2021), both while receiving rewards (Lockwood et al, 2018) and losses (Dugré et al, 2018). Previous studies further suggest that rostral and subgenual regions of the mPFC might be specialized in learning for others in social contexts (Lockwood et al, 2016;Christopoulos & King-Casas, 2015).…”
Section: Learning How Behavior May Benefit Self and Othersmentioning
confidence: 99%
“…As such, an individual’s social context can impact the rate of learning, as well as what is learned in a given situation depending on the developmental period. For instance, reinforcement learning models have been used to study how we update our expectations about others across development and how this is distinct from non-social learning (e.g., 58 63 ). Although the social context of learning warrants a review article of itself, we do want to highlight that the methods displayed in the current review are also valuable to apply to research that studies learning in a social context.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the development of learning for oneself compared to another person were also found in adolescence (aged 9-21). Learning for other showed more protracted development than learning for self, in both analysis of learning rates and relative brain activity (Westhoff et al, 2021).…”
Section: Social Vs Non-social Outcomesmentioning
confidence: 93%